(untitled) (Circe de clásicos y modernos, 2023)
This paper compares two anti-modern readings of Plato and the Platonic tradition, both complementary and opposite, that of Joseph de Maistre (1753-1821) and that of Joris-Karl Huysmans (1848-1907). These appropriations, which respectively open and closes the nineteenth century, express the rise and decline of the “romantic Platonism.” De Maistre quotes, comments on, translates and rewrites Plato’s dialogues, as well as various texts from the ancient Neoplatonism and the modern Platonic tradition. On the other hand, Huysmans’s texts, particularly À rebours (1884), the most representative novel of decadent aesthetics, express the crisis of romantic Platonism, as shown by its nihilism, the figure of the simulacrum and the modification of the androgynous topic. Thus, Platonism and its crisis explore historical temporality, from revolutionary acceleration to fin-de-siècle decadence.